BREEDING BIOLOGY OF INDIAN POND HERON BREEDING BIOLOGY OF INDIAN POND HERON BREEDING BIOLOGY OF INDIAN POND HERON Ardeola grayiis Ardeola grayiis Ardeola grayiis IN PUNJAB, INDIA - SUKHBIRPAL KAUR; TEJDEEP KAUR KLER (The Bioscan, 2018)
Study on breeding biology of Indian Pond Heron was conducted from February to December, 2017 in village Karamgarh (District Barnala) considered as location I and Punjab Agricultural University Campus, Ludhiana as location II. A total of 23 nests were located having clutch size 2 to 5 at both the locations. The overall maximum mean values of egg length 41.61 ± 0.97 mm and 39.08 ± 0.43 mm, egg width 29.71 ± 0.82 mm and 26.15 ± 0.66 mm, egg volume 16.36 cm3 and 11.12 cm3 at location I and II respectively. The average feeding frequency was 1.55 times/hour and 1.63 times/hour at location I and II respectively. Significant positive correlation of egg volume with egg length (r= 0.953) as well as with egg width (r=0.986) at location I was noted; it was not found at location II. There was negative correlation between egg volume and egg shape index (r = -0.259) at location I which was positive (r = 0.144) at location II. Location II which had higher hatching success had attributes like easy food availability due to crop diversity and nesting sites due to presence of indigenous trees.